Atributos desejáveis do (a) parceiro (a) ideal: valores e traços de personalidade como explicadores - Gonçalves, Marina Pereira (2012)
Understand how loving relationships are configured has been one of major field of interest in Psychology, mainly under an evolutionary and social perspectives. In this sense, the main goal of this thesis was to know how gender differences, human values and personality traits could explain the choice of the ideal partner. Thus, three empirical studies were accomplished. The study 1 aimed to identify affective and cognitive characteristics between men and women. Participated 208 heterosexual people, 108 men and 100 women, with age ranging between 18 and 52 years (m = 24,3 years; sd = 6,08). They have answered a questionnaire that assessed affective and cognitive characteristics. Related to cognitive aspects, men obtained higher scores than women in the studied constructs. On the other hand, women had higher scores on affective aspects than men, except on cooperation. These results highlights that gender differences might play an important role to understand the way people choose an ideal partner. The study 2 intended to verify differences among gender, human values and personality traits regarding to partner preference. Participated 244 people, mostly women (62,7%), with a mean age of 20,9 years (sd = 4,06). They answered to Attributes of Ideal Partner Scale (AIPS), Basic Values Questionnaire (BVQ), The Big Five Inventory and demographic questions. Beyond the relationship among studied variables, the main result of this study showed that human values mediate the relationship among personality traits and partners attributes. Lastly, aiming to replicate study 2, the study 3 was carried out. On this purpose, was counted with 3.124 people from each of nine Northeast states, divided in 49,3% living in the country and 50,7% living in the city, with a mean age of 23,6 years (sd = 6,72) and mostly women (63,6%). Participants answered the same questionnaire applied on study 2. The relationship among variables was found once again in this study, nevertheless, no significant differences were found among northeast states. A hierarchical regression was accomplished and identified that values are better predictors to partner preference than personality traits and demographic variables. It is reinforced that mediation models among personality traits and partners attributes by values found in the previous study were corroborated in all states and between country and city residents. It is expected that studies like this one might contribute to strengthen the knowledge in the loving relationship field.